2023
DOI: 10.1089/tmj.2022.0377
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Follow-Up Appointment No-Shows Before and During COVID Among Adults with Type 2 Diabetes

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has rapidly transformed health care delivery into telehealth visits. Attending regular medical appointments are critical to prevent or delay diabetes-related complications. Although telehealth visits have addressed some barriers to in-person visits, appointment no-shows are still noted in the telehealth setting. It is not completely clear how the predictors of appointment no-shows differ between in-person and telehealth visits in diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…in their study, sun et al found that hba 1C testing was performed 3 months later than the recommended time, and cancellation of referrals was more common during CoVid-19 than before. in addition, fewer referrals of diabetic patients was not a reason for poor blood sugar control [28]. however, the present study concluded that the delay in visiting a specialist doctor could cause an increase in hba 1C .…”
Section: Discussioncontrasting
confidence: 48%
“…in their study, sun et al found that hba 1C testing was performed 3 months later than the recommended time, and cancellation of referrals was more common during CoVid-19 than before. in addition, fewer referrals of diabetic patients was not a reason for poor blood sugar control [28]. however, the present study concluded that the delay in visiting a specialist doctor could cause an increase in hba 1C .…”
Section: Discussioncontrasting
confidence: 48%
“…During the COVID-19 pandemic, diabetes-related HbA 1c and nephropathy monitoring declined and did not recover to the prepandemic volume in the primary care setting [ 49 ]. A gap in timing between HbA 1c measurements was also a risk factor for missed appointments in the diabetes-specific setting [ 17 ]. To ensure care continuity and promote better outcomes, future research is warranted to investigate the ideal balance between in-person and telehealth visits in diabetes care.…”
Section: Discussionmentioning
confidence: 99%
“…The findings for this manuscript were the second part of a multimethod study focusing on missed appointments among adults with T2D. In short, the first part of the study used electronic health records (EHRs) to examine if predictors of missed appointments differ (1) between pre-COVID-19 (January 2019 to March 2020) and COVID-19 (March 2020 to December 2020) periods and (2) by health care delivery modes (in-person or telehealth visits) during COVID-19 among adults with T2D; more information is described elsewhere [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations